A FLY's view of salt inducible kinases: a synergistic tumorigenesis model - Sayın, Sercan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
The recent explosion of data generated by high-throughput assays on cancer necessitated reliable and fast in vivo models for evaluation new catalogue of candidate genes as tumor suppressors or proto-oncogenes and their subsequent trials in cancer therapeutics. Drosophila melanogaster, an acclaimed model organism for genetics studies, could now be proposed as the new pinnacle for modeling and screening those candidate genes. As an initiative study in Turkey, we tried to establish a multifaceted, synergistic cancer model based on the Drosophila compound eye, reinforced with fly glia and wing models, while using Salt Inducible Kinase (SIK) family as the choice of candidate genes. Metabolic deregulation in cancers is getting increased attention, thus SIKs were an excellent choice since they stand on the crossroad where metabolic and structural information in a cell meet. Using two backgrounds, low grade sensitized and high grade eyeful, we enquired the contributions on growth and metastasis by two existing Drosophila orthologs of human SIKs. Results showed that SIK2 could assume both suppressive and oncogenic roles; as optimal amounts of SIK2 could repress tumor growth while any fluctuations could enhance tumor and glial migration strength. SIK3, on the other hand, was found to act as oncogene when over-expressed in the studies. SIK3 gain could enforce several different outcomes; constitutive over-expression of SIK3 was highly lethal and could alter developmental fate choice of the respective context. Additionally, effects of SIKs on cancer tissues were investigated at cellular level via cell proliferation and death assays, which showed that SIKs could interact with major developmental pathways, such as Notch, TGF-β, FGF.
Keywords: Drosophila melanogaster.; Cellular signal transduction.; Carcinogenesis.